TPS3R Mojo Makmur Waste Processing Facility in Sustainable Waste Management - Baharintasari, Dinar Rachmadika; Utami, Trisni; Handoko, Chanel Tri (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2026)
This study analyzes household waste generation and the sustainability of the TPS3R Mojo Makmur waste management system in the City of Surakarta in response to increasing urban waste problems. The results show that household waste generation is still dominated by organic waste, while inorganic waste is relatively lower. Socioeconomic factors such as age, education level, and income do not significantly affect the total amount of waste generated but do influence waste composition. Multidimensional sustainability assessment indicates that TPS3R Mojo Makmur falls into the moderately sustainable category, with ecological and technological dimensions as its main strengths, particularly in waste reduction and the application of basic processing technologies. In contrast, the economic and socio-cultural dimensions remain challenging, especially in terms of limited economic value creation and suboptimal community participation. These findings highlight the need for policies that strengthen TPS3R institutional capacity, promote community-based circular economy development, and enhance public education and engagement. Support from local governments in the form of regulations, funding, and technological innovation is essential to improve the sustainability of integrated household waste management.